THE EFFECTIVENESS OF GAMIFICATION IN LEARNING ARABIC COHESIVE DEVICES (Keberkesanan Gamifikasi dalam Mempelajari Kata Penyambung dalam Bahasa Arab) - Mohd Ismath, Nurul Hanilah; Jalil, Siti Zubaidah; Tg Abdul Rahman, Tg Ainul Farha (Research & Innovation Management Centre (RMC), International Islamic University College Selangor (KUIS), Malaysia., 2022)
This research aims to identify the effectiveness of gamification in learning Arabic Cohesive Devices. Gamification refers to the application of game mechanics in non-game environments to enhance the enacted processes and the experience of its participants. The researcher used the quantitative descriptive approach and distributed the questionnaire using a survey method to 50 first- and second-year students from the University Sains Islam Malaysia. The questionnaire was distributed to the sample members through Google Form. Then, the researcher collected the data and used SPSS to analyze it and extract the means and standard deviations. From the search results, Gamification has a positive effect on students in higher education, especially in learning a foreign language, and through it, the process of learning Arabic Cohesive Devices increases the students' motivation. Finally, gamification provides the opportunity for learners to engage with content in an effective, informal learning environment